UZBEKISTAN’S ACCESSION TO THE WTO: LEGAL REFORMS AND CHALLENGES - Khumoyunmirzo Eshboev (Bright Mind Publishing, 2025)
Uzbekistan’s ongoing accession to the World Trade Organization (WTO) represents a pivotal transformation in its economic and legal architecture. This thesis investigates the complex legal adjustments and institutional reforms required for WTO membership. The study particularly focuses on legal harmonization with WTO agreements, the transition to a market economy governed by rules, and the challenges posed by aligning domestic law with international trade obligations. By examining comparative international models and the experience of other transitioning economies, this research identifies both challenges and strategic pathways for successful accession. This thesis also provides recommendations grounded in legal scholarship and Uzbekistan’s regulatory realities.
Keywords: WTO, legal reform, trade legislation, market economy, technical regulation, intellectual property.